C‐Myc‐mediated SNRPB upregulation functions as an oncogene in hepatocellular carcinoma. (22nd January 2020) - Peng, Ningfu; Li, Jindu; He, Jingrong; Shi, Xianmao; Huang, Hao; Mo, Yishuai; Ye, Hang; Wu, Guobin; Wu, Feixiang; Xiang, Bangde; Zhong, Jianhong; Li, Lequn; et al.
Abstract: Dysregulation of genes involved in alternative splicing contributes to hepatocarcinogenesis. SNRPB, a component of spliceosome, is implicated in human cancers, yet its clinical significance and biological function in hepatocellular carcinoma (HCC) remains unknown. Here, we show that SNRPB expression is increased in HCC tissues, compared with the nontumorous tissues, at both messenger RNA and protein levels in two independent cohorts. High expression of SNRPB is significantly associated with higher pathological grade, vascular invasion, serum alpha‐fetoprotein level, tumor metastasis, and poor disease‐free and overall survivals. Luciferase reporter and chromatin immunoprecipitation assays demonstrate that SNRPB upregulation in HCC is mediated by c‐Myc. Positive correlation is found between SNRPB and c‐Myc expression in clinical samples. In vitro studies show that ectopic expression of SNRPB promotes HCC cell proliferation and migration, whereas knockdown of SNRPB results in the opposite phenotypes. Collectively, our data suggest SNRPB function as an oncogene and serve as a potential prognostic factor in HCC.